2008
DOI: 10.1577/m06-184.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Assessment of Lake Sturgeon Population Structure in the Laurentian Great Lakes

Abstract: Many populations of lake sturgeon Acipenser fulvescens have decreased in size throughout the Great Lakes basin. To implement management strategies such as stocking, it is important to understand the genetic structure of lake sturgeon spawning populations. Lake sturgeon from 27 spawning locations (25 from the Great Lakes basin and 2 from the Hudson Bay drainage) were analyzed using 12 microsatellite loci. Population structure was detected at different spatial scales. At the largest scale, consistent genetic bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(121 citation statements)
references
References 65 publications
7
111
3
Order By: Relevance
“…Habitat degradation and fragmentation by dams continues to decrease their abundance and impede restoration efforts (Schueller and Hayes, 2011) by altering spawning behavior and reducing recruitment (Auer, 1996b;Haxton and Findlay, 2008). Despite significant declines in abundance, neither this study nor others (DeHaan et al, 2006;Drauch and Rhodes, 2007;Welsh et al, 2008;McDermid et al, 2011;Wozney et al, 2011) have observed significant decreases in genetic variability or evidence of inbreeding within populations of Lake Sturgeon. It is believed that the sturgeon are buffered from expected losses of genetic diversity because of their longevity and overlapping generations.…”
Section: Discussionmentioning
confidence: 53%
“…Habitat degradation and fragmentation by dams continues to decrease their abundance and impede restoration efforts (Schueller and Hayes, 2011) by altering spawning behavior and reducing recruitment (Auer, 1996b;Haxton and Findlay, 2008). Despite significant declines in abundance, neither this study nor others (DeHaan et al, 2006;Drauch and Rhodes, 2007;Welsh et al, 2008;McDermid et al, 2011;Wozney et al, 2011) have observed significant decreases in genetic variability or evidence of inbreeding within populations of Lake Sturgeon. It is believed that the sturgeon are buffered from expected losses of genetic diversity because of their longevity and overlapping generations.…”
Section: Discussionmentioning
confidence: 53%
“…The magnitude of genetic population differentiation strongly depends on the population status (wild or farmed) as well as the geographical scale of sampling (i.e., a stronger differentiation can be expected if the whole distribution range is covered compared to sampling within a single river, lake, or sea basin). Therefore, a comparison with available population genetic studies on lake sturgeon (McQuown et al 2003;Welsh et al 2008;Wozney et al 2011) and Siberian sturgeon (Barmintseva and Mugue 2017) would be suspect and was not attempted.…”
Section: Resultsmentioning
confidence: 99%
“…Extracted DNA was then analyzed at 12 disomic microsatellite loci (AfuG9, AfuG56, AfuG63, AfuG74, AfuG112, AfuG160, AfuG195, AfuG204, Aox27, Afu68, Afu68b, Spl120; Welsh and May 2006). Details on the protocol and variability of the loci are described in Welsh et al (2008). Genotypes from the 2005 samples were visualized using a BioRad BaseStation with an internal 400 ROX size standard.…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…The lowest allele frequency used was 0.02, and 95 % parametric confidence intervals were calculated. The effective population size (N e ) of the adult population in the Kaministiquia River (n=85; data published in Welsh et al 2008) was also computed to see whether N b in the larval cohorts reflects the overall N e in the population.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation